Supplementing tropical cattle for improved nutrient utilization and reduced enteric methane emissions - Ali, Asep I.M; Wassie, Shimels Eshete; Korir, Daniel; Merbold, Lutz; Goopy, John P.; Butterbach-Bahl, Klaus; Dickhoefer, Uta; Schlecht, Eva (MDPI, 2019)
Given their high nitrogen (N) concentration and low costs, sweet potato vine silage (SPVS) and urea-molasses blocks (UMB) are recommended supplements for tropical regions; therefore, they were investigated in this study. Six heifers were allocated to three diets: the roughage diet (R) consisted of wheat straw (0.61) and Rhodes grass hay (0.39; on dry matter (DM) basis); R + SPVS combined R (0.81) and SPVS (0.19); and with R + UMB animals had access to UMB. During two experimental periods, feed intake, feces and urine excretion, digesta passage, and rumen microbial protein synthesis were determined during seven days and methane emissions during three days. There was no treatment effect (p > 0.05) on DM and N intake. Apparent DM digestibility of R + SPVS (510 g/kg) was higher (p < 0.05) than of R (474 g/kg). Digesta passage and duodenal microbial N flow were similar for all diets (p > 0.05), while N retention was highest with R + SPVS (p > 0.05). Methane emissions per unit of digested feed (g CH4/kg dDM) were lower (p < 0.05) for R + SPVS (55.2) than for R (64.7). Hence, SPVS supplementation to poor–quality roughage has the potential to increase diet digestibility and N retention while reducing CH4 emissions.